Early Conversion From Calcineurin Inhibitor‐ to Everolimus‐Based Therapy Following Kidney Transplantation: Results of the Randomized ELEVATE Trial. Issue 7 (14th February 2017) - de Fijter, J. W.; Holdaas, H.; Øyen, O.; Sanders, J.‐S.; Sundar, S.; Bemelman, F. J.; Sommerer, C.; Pascual, J.; Avihingsanon, Y.; Pongskul, C.; Oppenheimer, F.; Toselli, L.; et al.
Abstract : In a 24‐month, multicenter, open‐label, randomized trial, 715 de novo kidney transplant recipients were randomized at 10–14 weeks to convert to everolimus (n = 359) or remain on standard calcineurin inhibitor (CNI) therapy (n = 356; 231 tacrolimus; 125 cyclosporine), all with mycophenolic acid and steroids. The primary endpoint, change in estimated glomerular filtration rate (eGFR) from randomization to month 12, was similar for everolimus versus CNI: mean (standard error) 0.3(1.5) mL/min/1.73 2 versus −1.5(1.5) mL/min/1.73 2 (p = 0.116). Biopsy‐proven acute rejection (BPAR) at month 12 was more frequent under everolimus versus CNI overall (9.7% vs. 4.8%, p = 0.014) and versus tacrolimus‐treated patients (2.6%, p < 0.001) but similar to cyclosporine‐treated patients (8.8%, p = 0.755). Reporting on de novo donor‐specific antibodies (DSA) was limited but suggested more frequent anti‐HLA Class I DSA under everolimus. Change in left ventricular mass index was similar. Discontinuation due to adverse events was more frequent with everolimus (23.6%) versus CNI (8.4%). In conclusion, conversion to everolimus at 10–14 weeks posttransplant was associated with renal function similar to that with standard therapy overall. Rates of BPAR were low in all groups, but lower with tacrolimus than everolimus. Abstract : In a multicenter, open‐label, randomized trial of de novo kidney transplant recipients, conversion to everolimus at 10–14 weeks posttransplant is associated with similar renal function as in patients who continue to standard tacrolimus or cyclosporine therapy, with low rates of biopsy‐proven acute rejection in all groups, but lower rates with tacrolimus than everolimus.